2009
DOI: 10.1016/j.ccr.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Rak Functions as a Tumor Suppressor by Regulating PTEN Protein Stability and Function

Abstract: Summary Expression of PTEN tumor suppressor is frequently lost in breast cancer in the absence of mutation or promoter methylation through as yet undetermined mechanisms. In this study, we demonstrated that the Rak tyrosine kinase physically interacts with PTEN and phosphorylates PTEN on Tyr 336. The knockdown of Rak enhanced the binding of PTEN to its E3 ligase, NEDD4-1, and promoted PTEN polyubiquitination, leading to PTEN protein degradation. Notably, ectopic expression of Rak effectively suppressed breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
179
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 22 publications
8
179
1
Order By: Relevance
“…RAK is a tyrosine kinase and may phosphorylate PTEN directly at Y336. 61 The function of these proteins may be lost in certain tumors and inhibition of their expression has been associated with tumorigenicity. 62,63 Other proteins interact with PTEN and inhibit its activity.…”
Section: Pseudo-pten and Other Oncogenes Decoys For Mirnasmentioning
confidence: 99%
“…RAK is a tyrosine kinase and may phosphorylate PTEN directly at Y336. 61 The function of these proteins may be lost in certain tumors and inhibition of their expression has been associated with tumorigenicity. 62,63 Other proteins interact with PTEN and inhibit its activity.…”
Section: Pseudo-pten and Other Oncogenes Decoys For Mirnasmentioning
confidence: 99%
“…However, from these studies, it is unclear as to whether the observed effects on PTEN function are attributable to its tyrosine phosphorylation or whether they are mediated indirectly through the phosphorylation of other SRC substrates. Recently, the RAK nonreceptor tyrosine kinase has been shown to enhance PTEN tumor suppressor function by phosphorylating tyrosine 336, thus preventing its degradation by the proteasome (15). This finding highlights the importance of accurately mapping the specific PTEN tyrosine residues phosphorylated in vivo and determining whether they have any role in clinical behavior or as predictors of relapse or indicators of prognosis.…”
mentioning
confidence: 91%
“…S6). These data suggest that FGFRs are highly specific Y240 kinases that may modulate PTEN function primarily through phosphorylation at this site, in contrast to SFKs, which regulate PTEN in a number of ways, presumably as a result of their ability to target multiple sites (13)(14)(15). Although PTEN has been shown to interact with platelet-derived growth factor receptors (PDGFRs) (22,23), which are closely related to FGFRs, neither PDGFRα nor EGFR drove robust phosphorylation of Y240 in our in vitro assays (SI Appendix, Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 Tyr336 phosphorylation is related to PTEN degradation. 33 In addition, Tyr240 and Tyr315 phosphorylation could help to maintain phosphatase function of PTEN. 34,35 Bolduc et al 16 found that upon phosphorylation of the 380-385 Ser/Thr cluster, the PTEN C-terminal modified tail clamps down intramolecularly on the C2 domain, preventing PTEN from binding to the plasma membrane and reducing its catalytic action toward PIP3.…”
Section: Regulation Of Pten Functionsmentioning
confidence: 99%